A Benchmarking of the Undergraduate Economics Major in Europe and in the United States - Monteiro, H.; Ferreira-Lopes, A. (International Review of Economics Education, 2007)
We compare the undergraduate Economics majors and their underlying structure in the top-ranked Economics departments of Europe and the USA, identifying the fundamental courses included in an Economics major in top-ranked universities. We further distinguish between those courses that are required and those that are usually offered as electives, finding striking differences between Europe and the USA, especially regarding the nature of the main electives offered. The insights from this comparative study may be useful for the ongoing restructuring of undergraduate Economics majors in European countries caused by the Bologna Process.